Assessing the impact of land use change on aridification in semiarid land. (17th August 2018) - Emadodin, Iraj; Reinsch, Thorsten
Abstract: In this study, aridification as an environmental challenge was investigated in detail. Regional meteorological data and climate indices as diagnostic tools have been used to detect the temporal trend of aridification over the past six decades in Tehran City. For this purpose, annual time‐series (1951–2010) of temperature, precipitation, relative humidity, and visibility as well as the climate indices (Johansson continentality index, De Martonne aridity/humidity index, Pinna combinative index, discomfort index, and potential evapotranspiration) have been selected. The study focuses on Tehran, the largest urban area in western Asia and a complex socio‐economic region (with around 8.3 million people). Mann–Kendall test was used to determine temporal trends in the climate indices and meteorological data. The results show that the climate components are strongly affected by the rapid urbanization and land‐use change during the last six decades. The De Martonne and Pinna combinative indices show high variations in the analyzed periods. The results show positive trend in visibility and temperature. Discomfort condition and potential evapotranspiration have been calculated for two separate temporal periods (1951–1975 and 1976–2010). Temporal distribution of discomfort index shows more than half of the population feels discomfort in July after rapid urbanization during 1976–2010. The potential evapotranspiration shows an increase during 1976–2010 period compared with the 1951–1975 period. The threshold of growing aridity in the area under investigation is mainly due to an increase of annual temperature that effects on the potential evapotranspiration.